Divergent and conserved features in the spatial expression of the Drosophila pseudoobscura esterase-5B gene and the esterase-6 gene of Drosophila melanogaster - Tamarina, Natalia A. (The National Academy of Sciences of the USA, 1997)
The regulatory regions of homologous genes encoding esterase 6 (Est-6) of Drosophila melanogaster and esterase 5B (Est-5B) of Drosophila pseudoobscura show very little similarity. We have undertaken a comparative study of the pattern of expression directed by the Est-5B and Est-6 5′-flanking DNA to attempt to reveal conserved elements regulating tissue-specific expression in adults. Esterase regulatory sequences were linked to a lacZ reporter gene and transformed into D. melanogaster embryos. Est-5B, 5′ upstream elements, give rise to a β-galactosidase expression pattern that coincides with the wild-type expression of Est-5B in D. pseudoobscura. The expression patterns of the Est-5B/lacZ construct are different from those of a fusion gene containing the upstream region of Est-6. Common sites of expression for both kinds of constructs are the third segment of antenna, the maxillary palps, and salivary glands. In vitro deletion mutagenesis has shown that the two genes have a different organization of regulatory elements controlling expression in both the third segment of antenna and maxillary palps. The results suggest that the conservation of the expression pattern in genes that evolved from a common ancestor may not be accompanied by preservation of the corresponding cis-regulatory elements.